Defect and Doping Engineered Penta-graphene for Catalysis of Hydrogen Evolution Reaction - Jinbo Hao; Feng Wei; Xinhui Zhang; Long Li; Chunling Zhang; Dan Liang; Xiaoguang Ma; Pengfei Lu (Nanoscale Research Letters, 2021)
Abstract Water electrolysis is a sustainable and clean method to produce hydrogen fuel via hydrogen evolution reaction (HER). Using stable, effective and low-cost electrocatalysts for HER to substitute expensive noble metals is highly desired. In this paper, by using first-principles calculation, we designed a defect and N-, S-, P-doped penta-graphene (PG) as a two-dimensional (2D) electrocatalyst for HER, and its stability, electronic properties and catalytic performance were investigated. The Gibbs free energy (ΔG H), which is the best descriptor for the HER, is calculated and optimized, the calculation results show that the ΔG H can be 0 eV with C2 vacancies and P doping at C1 active sites, which should be the optimal performance for a HER catalyst. Moreover, we reveal that the larger charge transfer from PG to H, the closer ΔG H is to zero according to the calculation of the electron charge density differences and Bader charges analysis. Ulteriorly, we demonstrated that the HER performance prefers the Volmer–Heyrovsky mechanism in this study.